Analysis of the Suitability of Road Signs and Markings for One-Way Traffic on Jalan Kartini, Tegal City - Veda Widyadhana Aji; Rania Ratu Khairani; Febyana Dwi Salsa Abidin; Suprapto Hadi; Brasie Pradana Sela Bunga Riska Ayu (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2026)
Urban road networks face increasing challenges due to rapid vehicle growth and the complexity of traffic dynamics, especially in medium-sized cities such as Tegal, Indonesia. Jalan Kartini is a vital road segment with high economic and pedestrian activity that often experiences congestion and irregular traffic flow. To address these issues, this study aims to evaluate the traffic performance of Jalan Kartini and to assess the suitability of existing road signs and markings for supporting the implementation of a one-way traffic system on this corridor. A descriptive evaluative method was employed, using field surveys and traffic observations, including traffic volume, vehicle speed, degree of saturation, and road capacity results, as well as the condition of road signs and markings. Results showed that the highest traffic volume is 609 PCU/h, with the score of road capacity is 1288.87 PCU/h and score of degree saturation is 0.37 which is indicating a good service level. The 85th percentile speed was recorded at 49 km/h, which is close to the upper limit of the design speed range for secondary collector roads (30–50 km/h) and exceeds the posted speed limit of 30 km/h on Jalan Kartini. However, significant issues were identified in the physical condition and visibility of traffic signs and road markings, many of which were faded, improperly placed, or did not meet regulatory dimensions. The study concludes that although the traffic performance supports a one-way system, the current infrastructure, including signage and markings must be revitalized to ensure effectiveness and safety. This research contributes to urban traffic management practices by highlighting the critical role of visual infrastructure in supporting directional traffic policy implementation.